Boosting Their Stomachs’: The Role of Social Grants in South Africa - Gutura, Priscilla (Journal of Economics and Behavioral Studies, 2014)
The findings of this paper emanates from a broader research that was conducted to examine the role of social grants on poor rural households in Ngqushwa Municipality in the Eastern Cape Province of South Africa. The study adopted a methodological triangulation approach in data collection and analysis. Five hundred (500) questionnaires were distributed among social grant beneficiaries who were selected using multi-stage sampling. These yielded quantitative results which were then complemented by qualitative results obtained from 25 in-depth interviews and 2 focus group discussions conducted with 16 participants. One of the objectives of the broader study was to explore the role of social grants in tackling the vulnerability of beneficiaries to hunger. The major findings of the study point to the fact that the greatest discretion of spending is on food. This has improved food accessibility and availability among beneficiaries and has most importantly reduced both child and adult hunger in households where social grants are injected. Social grants have no doubt reduced hunger and sufferings among beneficiaries. However with the economic downturn and escalating food prices, the nutritional value is lower and beneficiaries remain in poverty as they are not food secure.